(untitled) (Baghdad Science Journal, 2010)
The present work aimed to study the effect of Grave’s disease on the different tissues and organs of the body by using Wayne Thyrotoxicosis Diagnostic Index (WTDI) and Basel Metabolic Index (BMI). To reach such aim, (35) patients were involved (25 females and 10 males). A control group of (15) healthy individuals (10 females and 5 males) was selected for comparison , as well as , the following: 1- Wayne Thyrotoxicosis Diagnostic Index (WTDI) applied on patient group and control group under the supervision of specialist medical team , this index include (19) sign and symptom , the appearance of one of them may be lead to the others. The sings and symptoms of the index appear only on the patients. There is no Significant differences between the replications of the sings and symptoms between the female patient and the male patients.2- Basel Metabolic Index (BMI) applied on the patient group and control group , Significant decrease in the mean values of Basel Metabolic Index (BMI) was appeared in comparison with control group.